The Comparative Effects of Valsartan and Amlodipine on vWf Levels and N/L Ratio in Patients with Newly Diagnosed Hypertension. (November 2013) - Karaman, Murat; Balta, Sevket; AY, Seyit Ahmet; Cakar, Mustafa; Naharci, Ilkin; Demirkol, Sait; Celik, Turgay; Arslan, Zekeriya; Kurt, Omer; Kocak, Necmettin; Sarlak, Hakan; Demirbas, Seref; et al.
<x xml:space="preserve">Abstract</x> High levels of circulating Von Willebrand factor (vWf) and increased neutrophil to lymphocyte (N/L) ratio may reflect vascular inflammation in hypertensive patients. In present study, we aimed to investigate the effects of valsartan as an angiotensin II receptor antagonist and amlodipine as a calcium channel blocker on the vWf levels and N/L ratio in patients with essential hypertension. Patients were randomized to one of the following intervention protocols: calcium channel blocker (amlodipine, 5–10 mg/day) as group A (n = 20 mean age = 51.85 ± 11.32 y) and angiotensine II receptor blocker (valsartan, 80–320 mg/day) as group B (n = 26 mean age = 49.12 ± 14.12 y). Endothelial dysfunction and vascular inflammation were evaluated with vWf levels and N/L ratio in hypertensive patients before treatment and after treatment in the 12th week. No statistically significant differences were found among the groups in terms of age, sex, and body mass index (BMI). There was a significant decrease in vWf levels (P < .001) and N/L ratio after treatment (P = .04, P < .001, respectively) in both the groups. Von Willebrand factor levels and N/L ratio are very important markers having a role in vascular inflammation and antihypertensive treatment with amlodipine and valsartan may improve cardiovascular outcomes by decreasing these biomarkers.